Better Than Friends: Sunrise Cove #7 - Shalvis, Jill (New York, NY : Avon, an imprint of HarperCollins Publishers, 2025)
When Olive Porter's off-the-grid parents go missing, she reluctantly seeks out Noah Turner, her ex and the only person she both trusts implicitly and not at all. As a special investigative agent for the National Park Service, Noah's used to living under intense pressure. Or he was until he got injured on the job. Now unhappily recuperating at home while being smothered by his loving but nosy family, he'd love nothing more than a good distraction. So when Olive shows up looking like a million bucks, he has to do a gut and heart check. Because nope, no matter what, he can't fall for her again, the woman who once blew up his entire life and never looked back. How ironic then that his own personal hell (Olive) is also his ticket out of town. The question is, will the risk be worth the reward?
Includes a sneak peek of the author's The love fix.
new book 2025 winter.
Keywords: Missing persons -- Fiction; Man-woman relationships; Park rangers -- Fiction; Romance fiction